A new silky lacewing (Neuroptera: Psychopsidae) from the Middle Jurassic of Inner Mongolia, China - Peng, Yuanyuan; Makarkin, Vladimir N.; Yang, Qiang; Ren, Dong (Zootaxa, 2010)
Cretapsychops decipiens sp. nov. is described from the Middle Jurassic Jiulongshan Formation of Daohugou, Inner Mongolia in China. The new species is distinguished from the type species known from the Early Cretaceous Wealden Supergroup of England mainly by its longer costal gradate series and distinctive colour pattern of the forewings. The disruptive coloration of its forewings may perform a defensive (concealment) function. The structure of CuA is peculiar in Cretapsychops and is different from that of all other known psychopsid genera.